HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR PESERTA DIDIK DI SD TAKHASSUS AL-QURAN - Ayu Sholina; Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
ABSTRACT This study was motivated by the low emotional intelligence and academic achievement of students in SD Takhassus al-Quran Kalibeber Wonosobo. Theory of this study is emotional intelligence theory from Daniel Goleman. This study aims to investigate the relationship between emotional intelligence and academic achievement of students grade VI B SD Takhassus Al-Quran Kalibeber Wonosobo. The methode used in this study was mixed method with sequential exlanatory design. Data collection techniques used were emotional intelligence and self-regulated learning scales, observation, and interview, data analysis techniques used analysis correlate bivariate. The result showed that there was a significant relationship between emotional intelligence (X) and academic achievement (Y) as evidencedby the result of interview which showed that student who has high emotional intelligence has high academic achievement too. The student who has low emotional intelligence has low academic achievement too.